Tumor promoting effects of cyanobacterial extracts are potentiated by anthropogenic contaminants--evidence from in vitro study - Nováková, Kateřina; Bláha, Luděk; Babica, Pavel (Chemosphere, 2012)
Inhibition of gap junctional intercellular communication (GJIC) is affiliated with tumor promotion process and it has been employed as an in vitro biomarker for evaluation of tumor promoting effects of chemicals. In the present study we investigated combined effects of anthropogenic environmental contaminants 2,2',4,4',5,5'-hexachlorobiphenyl (PCB 153) and fluoranthene, cyanotoxins microcystin-LR and cylindrospermopsin, and extracts of laboratory cultures of cyanobacteria Aphanizomenon gracile and Cylindrospermopsis raciborskii, on GJIC in the rat liver epithelial cell line WB-F344. Binary mixtures of PCB 153 with fluoranthene and the mixtures of the two cyanobacterial strains elicited simple additive effects on GJIC after 30 min exposure, whereas microcystin-LR and cylindrospermopsin neither inhibited GJIC nor altered effects of PCB 153 or fluoranthene. However, synergistic effects were observed in the cells exposed to binary mixtures of anthropogenic contaminants (PCB 153 or fluoranthene) and cyanobacterial extracts. The synergistic effects were especially pronounced after prolonged (6-24h) co-exposure to fluoranthene and A. gracile extract, when mixture caused nearly complete GJIC inhibition, while none of the individual components caused any downregulation of GJIC at the same concentration and exposure time. The effects of cyanobacterial extracts were independent of microcystin-LR or cylindrospermopsin, which were not detected in cyanobacterial biomass. It provides further evidence on the presence of unknown tumor promoting metabolites in cyanobacteria. Clear potentiation of the GJIC inhibition observed in the mixtures of two anthropogenic contaminants and cyanobacteria highlight the importance of combined toxic effects of chemicals in complex environmental mixtures.
Keywords: Environmental Pollutants; karcinogeny; látky znečišťující životní prostředí; Cell Line; epitelové buňky; buněčné extrakty; fluoreny; Rats; Cell Communication; Fluorenes; Aphanizomenon; polychlorované bifenyly; alkaloidy; Cylindrospermopsis; Uracil; Cell Extracts; mořské toxiny; Epithelial Cells; Alkaloids; Drug Synergism; Marine Toxins; krysa rodu Rattus; uracil; Bacterial Toxins; toxiny kmene Cyanobacteria; Polychlorinated Biphenyls; bakteriální toxiny; synergismus léků; zvířata; Microcystins; mikrocystiny; Carcinogens; mezerový spoj; buněčné linie; Gap Junctions; Cyanobacteria Toxins; mezibuněčná komunikace; Animals